Clustering of carbon quantum dots from polysaccharides (Cellulose, Alginate, Chitosan) versus heterocyclic compounds: Synthesis, characterization and medical applications - Hanan B. Ahmed; Mary M. Mikhail; Mahmoud El-Shahat; Hossam E. Emam (Carbohydrate Polymer Technologies and Applications)
Carbon quantum dots are special class of carbon nanostructures with spherical size of one to ten nanometers. Synthesis techniques of carbon quantum dots are diverse from top-down to bottom-up techniques but most of them are complicated, energy consuming, time-consuming and expensive. However, the hydrothermal technique has advantages of high yield, easy control and simplicity than other synthesis methods. Due to high availability of carbon precursors, biocompatibility, high surface area, low cost, high photostability and low cytotoxicity properties of carbon quantum dots, they have diverse medical applications which are currently summarized in the presented review. The current review represents an overview for the compatibility and superiority of polysaccharides (e.g. pectin, alginate, cellulose, chitosan) versus heterocyclic compounds for successive clustering of carbon quantum dots.